Psychometric evaluation of the German Version of the Supportive Care Needs Survey for Partners and Caregivers (SCNS‐P&C‐G) of cancer patients. (5th May 2015) - Sklenarova, H.; Haun, M.W.; Krümpelmann, A.; Friederich, H.‐C.; Huber, J.; Thomas, M.; Winkler, E.C.; Girgis, A.; Dinkel, A.; Herzog, W.; Hartmann, M.
<x xml:space="preserve">Abstract</x> This study aimed for psychometric validation of the German version of the Supportive Care Needs Survey for Partners and Caregivers (SCNS‐P&C‐G). In‐ and outpatients with lung, urological and gastrointestinal cancer at Heidelberg University Hospital in Germany and in each case one relevant caregiver were asked to complete a set of questionnaires assessing their unmet needs together with distress, depression, anxiety and caregiver strain. In addition, medical data of the patients were collected. Fully completed questionnaires were received from 188 pairs of patients and their caregivers. Using exploratory factor analysis, four domains of unmet needs were identified with an appropriate variance explanation (58.7%) and acceptable (>0.70) internal consistencies (α = 0.95 to 0.76) for each domain. Convergent validity was found with respect to significant positive correlations (>0.40) of the SCNS‐P&C‐G domains with caregivers' anxiety, depression and strain. Although poorer health status of the patient indicated more unmet caregiver needs, this finding was not consistent for all need domains. Overall, associations were only moderate to weak pointing out the necessity of a separate screening for caregivers' needs. The findings of this study support that the SCNS‐P&C‐G is an appropriate research instrument to assess caregivers' needs on different domains throughout the disease trajectory.